Pre-treatment and Classification of Cathode Active Material from Used Lithium-Ion Batteries (LIBs) - Alfred Obaje; Douglas Onyancha; Samuel Mirie (Chemical and Materials Sciences: Developments and Innovations Vol. 10, 2025)
In portable devices and electric cars, lithium batteries have become more common due to their benefits in environmentally friendly operations, high energy density, extended storage life compact volume, lightweight, vast range of application temperatures, and low self-release of power efficiency. The development of lithium-ion batteries (LIBs) for use in electric vehicles, portable electronic devices, and energy-storage devices has resulted in an increase in the quantity of used LIBs. The environment and public health are seriously endangered by the hazardous metals found in spent LIBs, for example, Cobalt and Manganese metals, with a poisonous caustic electrolyte, and binders of organic origin. Based on these factors, procedures for recycling LIBs that are efficient, affordable, also benign to the environment are being developed in order to ensure a long-term sustainable future solution. In this research, used lithium batteries were released into a sodium chloride solution with a lower concentration, manual dismantling of LIBs components, and separations of components such as cathode, anode, plastic casing, separators, and electrolyte. Also, the dissolution of cathode material in sodium hydroxide solutions and finally characterized the cathode electrode, using an X-ray fluorescence spectrometer (XRF) and Thermogravimetric analysis (TGA). The Polyvinylidene fluoride (PVDF) and diethyl carbonate (DEC) particles in raw cathode material, detected by Fourier Transform infrared (FT-IR) analysis, were effectively thermally decomposed at 464.98 °C and 150 °C respectively. The XRF analysis of thermally treated cathode material powder showed the presence of: 61.72 % of Co, 12.11 % of Ni, 9.64 % of Mn, and 16.53 % of other components. The FT-IR analysis and thermogravimetric analysis, clearly showed the presence of Polyvinylidene fluoride and Diethyl carbonate, this can be successfully eliminated through thermal disintegration as evidenced by TGA analysis.